Only 17,000 Minutes till Our Next Vacation - Nettleton, Greta (The Quack's Daughter, 2013)
Marian Austin first appears in Cora’s diary on a brisk March day in 1885: “A ‘Windy’ day so I wore my ‘sky blue’ veil. It was much becoming to me. Marian wore hers also. After drifting with the wind for 20 or so minutes we finally settled on a subject—spreads. I concluded I would have mine after my sojourn in New York City, on the 14th or the 21st of March. This seemed a suitable time, as I could purchase things at Macys, Candi’s etc.” Bundled up in warm scarves, the two young women, one tall and one short,